THE ROLE OF RENEWABLE ENERGY IN THE DEVELOPMENT OF THE "GREEN ECONOMY" - Nasirkhodjaeva Dilafruz Sabitkhanovna; Rakhimova Mohkinur Dilshod kizi (American Journals, 2023)
This article provides information about the essence of the renewable energy source and the work carried out in Uzbekistan.
Keywords: renewable energy, environmental sustainability, environmental problems